(3GdeSFhdjI GdeOfjI Yf YedjGJ fbd hRQY GdCYVGA GdHTQjI (B/s - (3RGgQ, eMeO UdGM GdOjf YHO GdYXjes ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3jJMOK GdcJGH Yf GdeSFhdjI GdeOfjI Yf YedjGJ fbd hRQY GdCYVGA GdHTQjI MjK CJjM ddCWHGA aj Xd GdJWhQ GdgGFd ddCWHGA GSJNOGe CMOK GdCSGdjH Ydi CYVGA GdLfS GdHTQj HZjI ELQGA YedjGJ fbd hRQY GdCYVGA GdHTQjI ShGA ef GdCMjGA hGdehJi hYdi CKQ Pdc JfTC eTcdGJ YOI ajeG jJYdb HeHOC eYUhejI GdLSO hCNQi aj JMOjO eYjGQ KGHJ hMbjbj dehJ GdTNU ai GdbGfhf hGdTQY hGdWH(B.s
(3HHdjhLQGajI (B: (3UaMI (B331-344.s
Keywords: (3RQY GdCYVGAs -- (3bhGfjf hJTQjYGJs; (3fbd GdCYVGAs -- (3bhGfjf hJTQjYGJs; (3GdWHs -- (3bhGfjf hJTQjYGJs; (3LSe GdEfSGfs -- (3bhGfjf hJTQjYGJs; (3GdbGfhf GdLfGFjs; (3GdeSDhdjI GdeOfjI s; (3JLGQI GdCYVGA GdHTQjIs